First record of Gastrodia (Orchidaceae, Epidendroideae) from Brunei Darussalam - Hroneš, Michal; Sochor, Michal; Jaafar, Salwana; Sukri, Rahayu S.; Dančák, Martin (Phytotaxa, 2024)
The occurrence of Gastrodia sabahensis is reported for the first time from Brunei Darussalam representing the new generic record for the country. Morphological description based on the discovered plants along with photo plates, notes on distribution, ecology and conservation status have been provided. Additionally, a determination key for all Gastrodia species in Borneo is presented for the first time.